Financial Risks Contained in Current Local Government Debt and Preventive Measures - Zhang, Xin (Journal of Theory and Practice of Social Science, 2023)
Since the financial crisis in 2009, local government debt has been increasing in our country, huge amount, and sweep scope. If the local government's debt is unable to repay, it will trigger a national subprime mortgage crisis, and even make the whole financial industry in danger, which will have a great impact on our national economy. In this regard, we must carefully analyze the financial risks of local government debt and put forward effective preventive measures.